Menginjak Gas Mencari Tuhan: Esai Reflektif Mengenai Kaum Pinggiran di Kota Malang - Ramadhani, I Gusti Ngurah Aswin (Perspektif, 2011)
The article argues way of life of the Javanese, particularly those who live in the pheriphery of the society, the so-called people of the margins. They believe that God has provided everything for everybody that should be accepted faithfully, for God is the One who is full of love and compassion. In so doing, everybody, no matter which social group he/she belongs to will live his/her life in thankfulness, fidelity, and honesty. The Javanese call it nerima ing pandum, a kind of local genius enlivened by kawruh kejawen (Javanese gnosis). Based on this religiosity which corresponds to Benedictine tradition of ora et labora, the writer then reflects theologically the way people in the industrilized world of today should deal with their daily lives. We can learn a lot from people of the margins how to manage our personal lives as well as to organize our community in God's providence.